Neurotoxicity following CD19/CD28ζ CAR T-cells in children and young adults with B-cell malignancies. Issue 9 (11th February 2022) - Shalabi, Haneen; Martin, Staci; Yates, Bonnie; Wolters, Pamela L; Kaplan, Claire; Smith, Hannah; Sesi, Christopher R; Jess, Jennifer; Toledo-Tamula, Mary Anne; Struemph, Kari; Delbrook, Cindy P; Khan, Omar I; et al.
Abstract: Background: Neurotoxicity is an established toxicity of CD19 CAR T-cell therapy; however, there is little information on neurotoxicity in children, adolescents, and young adults (CAYA) receiving CD19/CD28ζ CAR T-cells for B-cell malignancies. Methods: We analyzed neurotoxicity of CD19/CD28ζ CAR T-cells in CAYA treated on a phase I study (NCT01593696). Assessments included daily inpatient monitoring, caregiver-based neuro-symptom checklist (NSC), exploratory neurocognitive assessments, clinically-indicated imaging, CSF analysis, and systematic cytokine profiling, outcomes of which were associated with cytokine release syndrome (CRS) and treatment response postinfusion. Patients with active CNS leukemia were included. Results: Amongst 52 patients treated, 13 patients had active CNS leukemia at infusion. Neurotoxicity was seen in 11/52 (21.2%) patients, with an incidence of 29.7% (11/37) in patients with CRS. Neurotoxicity was associated with the presence and severity of CRS. Those with neurotoxicity had higher levels of peak serum IL-6, IFNγ, and IL-15. Additionally, CNS leukemia was effectively eradicated in most patients with CRS. Pilot neurocognitive testing demonstrated stable-to-improved neurocognitive test scores in most patients, albeit limited by small patient numbers. The NSC enabled caregiver input into the patient experience. Conclusions: This is the first systematic analysis of neurotoxicity utilizing a CD19/CD28ζ CAR construct in CAYA, including in those with active CNS involvement. The experience demonstrates that the neurotoxicity profile was acceptable and reversible, with evidence of anti-leukemia response and CNS trafficking of CAR T-cells. Additionally, neurocognitive testing, while exploratory, provides an opportunity for future studies to employ systematic evaluations into neurotoxicity assessments and validation is needed in future studies.